Constructing Responsible Artificial Intelligence Principles as Norms: Efforts to Strengthen Democratic Norms in Indonesia and European Union - Rofi Aulia Rahman; Valentino Nathanael Prabowo; Aimee Joy David; József Hajdú (Faculty of Law, Universitas Padjadjaran, 2022)
Artificial Intelligence influences democratic norms and principles. It affects the quality of democracy since it triggers hoaxes, irresponsible political campaign, and data privacy violations. The study discusses the legal framework and debate in the regulation of Artificial Intelligence in the European Union legal system. The study is a doctrinal legal study with conceptual and comparative approach. It aims to criticize the current doctrine of democracy. The analysis explored the law on election and political party in Indonesia to argue that the democratic concept is outdated. On the other hand, the European Union has prepared future legal framework to harmonize Artificial Intelligence and democracy. The result of the study indicates that the absence of law on Artificial Intelligence might be the fundamental reason of the setback of democracy in Indonesia. Therefore, the Indonesian legal system must regulate a prospective Artificial Intelligence regulation and a new democratic concept by determining the new principles of responsible Artificial Intelligence into drafts of laws on Artificial Intelligence, election, and political party. Finally, the new laws shall control programmers, politicians, governments, and voters who create and use Artificial Intelligence technology. In addition, these legal principles shall be the guideline to prevent the harms and to mitigate the risks of Artificial Intelligence technology as well as the effort to strengthen democracy.DOI: https://doi.org/10.22304/pjih.v9n2.a5